Applying Human Right - Based Approach in Constitutional Rights Guarantee in Vietnam - Duong, Nguyen (VNU Journal of Science: Legal Studies; Vol 36 No 2DO - 10.25073/2588-1167/vnuls.4265, 2020)
The provisions on human rights and civil rights in the  2013 Constitution have marked a progress in constitutional reform. However, the implementation of constitutional rights have still faced many challenges in practice. One of these challenges is inappropriate awareness on human rights of public actors as well as the people. A rights-based approach, an approach that pays equal attention to what should be done and to how it should be done, will contribute to better constitutional rights realization by raising both awareness of right-holders and the sense of responsibility of duty-bearers. Keywords: human right-based approach, human rights, constitutional rights implementation. References: [1] OHCHR, Frequently Asked Questions on the Human Rights-based Approach in Development Cooperation, 2006, p.1. https://www.ohchr.org/Documents/Publications/FAQen.pdf (Truy cập: 15/11/2019). [2] United Nation Vietnam, Giải thích sơ lược về Phương pháp tiếp cận dựa trên cơ sở Quyền Con người (Tài liệu dành cho Cán bộ Liên hợp quốc tại Việt Nam). http://www.un.org.vn/images/stories/pub_trans/HRBA_Toolkit_-_Vietnamese.pdf (Truy cập: 15/11/2019). [3] Ủy ban về Quyền con người, Bình luận chung số 25 (1996). [4] Trung tâm Nghiên cứu QCN &QCD, Khoa Luật, ĐHQGHN, Giới thiệu về các quyền dân sự và chính trị, NXB Hồng Đức, 2012. [5] Secretary-General, Guidance Note of the Secretary-General: United Nations Assistance to Constitution-making Processes. https://www.un.org/ruleoflaw/files/Guidance_Note_United_Nations_Assistance_to_Constitution-making_Processes_FINAL.pdf (Truy cập: 15/11/2019). [6] World Bank, Governance: The World Bank’s Experience, Washington DC, 1994, p. VII. [7] Secretary-General, Guidance Note of the Secretary-General: UN Approach to Rule of Law Assistance. [8] Secretary-General, Guidance Note of the Secretary-General: United Nations Assistance to Constitution-making Processes. https://www.un.org/ruleoflaw/files/Guidance_Note_United_Nations_Assistance_to_Constitution-making_Processes_FINAL.pdf (15/11/2019). [9] Secretary-General, Guidance Note of the Secretary-General on Democracy. [10] United Nations Viet Nam, Human rights and the human rights-based approach. http://www.un.org.vn/en/what-we-do-mainmenu-203/cross-cutting-themes-human-rights.html (15/11/2019). [11] OHCHR, Human rights and Constitution making, New York & Geneva, 2018, p. 3 - 10. https://www.ohchr.org/Documents/Publications/ConstitutionMaking_EN.pdf (15/11/2019). [12] Vũ Công Giao, Những tiến bộ và hạn chế trong chế định quyền con người, quyền công dân của Dự thảo 3 Hiến pháp 1992 sửa đổi năm 2013, Tạp chí Khoa học ĐHQGHN, Luật học,Tập 29, Số 3 (2013) 52-63. [13] Đào Trí Úc - Vũ Công Giao, “Khái quát những điểm mới của Hiến pháp năm 2013” trong cuốn Bình luận khoa học Hiến pháp nước Cộng hòa xã hội chủ nghĩa Việt Nam Việt Nam năm 2013 (Sách chuyên khảo), NXB ĐHQGHN, 2014. [14] Nguyễn Thùy Dương, “Tiếp cận dựa trên quyền trong xây dựng, thực hiện chính sách, pháp luật về quyền của phụ nữ ở Việt Nam” trong cuốn “Tiếp cận dựa trên quyền con người - Lý luận và thực tiễn” (Sách chuyên khảo), NXB ĐHQGHN, 2016. [15] Lã Khánh Tùng, Cơ quan Nhân quyền quốc gia 101 Câu hỏi - đáp, NXB Hồng Đức, 2017, tr. 5-10. [16] Strengthening the National Human Rights Protection System. http://www.globalequality.org/storage/documents/pdf/manual%20nhrps-web.pdf (15/11/2019). [17] Khoa Luật, ĐH QGHN, Giới thiệu các văn kiện quốc tế về quyền con người, NXB Lao động - xã hội, 2011, tr.821-824. [18] Lã Khánh Tùng, Vũ Công Giao, Bài viết “Giáo dục về Quyền con người ở Việt Nam hiện nay” trong Kỷ yếu Hội thảo Kết nối Nghiên cứu về Quyền con người, 8/2008.